Imetelstat for treatment of myelofibrosis. (2nd January 2017) - Virtgaym, E.; Tremblay, D.; Iancu-Rubin, C.; Hoffman, R.; Mascarenhas, J.
ABSTRACT: Introduction : Myelofibrosis (MF) is a myeloproliferative neoplasm associated with peripheral blood cytopenias, marrow fibrosis, splenomegaly systemic symptoms and evolution to a refractory form of acute myeloid leukemia. Treatment with a JAK1/2 inhibitor significantly improves the symptom burden and reduces the degree of splenomegaly. JAK1/2 therapy, however, results in a modest prolongation of survival, but does not halt disease progression or reduce the risk of leukemic transformation. Novel agents with the potential to alter the progressive disease course of MF are urgently needed. Areas covered : The pre-clinical rationale for the use of the telomerase inhibitor, imetelstat, in patients with advanced MF and essential thrombocythemia (ET) will be reviewed as well the results of the initial clinical trials with this agent. Expert opinion : Results from a single institution pilot study of imetelstat therapy have been reported and indicate a signal of activity. This approach appears to have the potential to reverse bone marrow histomorphologic abnormalities, induce molecular responses, and target the malignant hematopoietic stem cell population in MF patients. Results from a randomized, multi-center, phase II trial in MF are ongoing.